2019
DOI: 10.5114/ada.2019.82822
|View full text |Cite
|
Sign up to set email alerts
|

The safety of isotretinoin treatment in patients with bone fractures

Abstract: Isotretinoin is widely applicable in dermatology, although it may develop severe side effects in the skeletal system. An intention of this review was to establish the safety of oral isotretinoin in patients with bone fractures. Both MEDLINE/Pubmed and SCOPUS databases were searched to investigate the influence of isotretinoin on the skeletal system. The drug shows a strong osteoporotic activity in rats whereas this effect is milder in humans. Biochemical markers of bone turnover remain unchanged except for ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
0
16
0
5
Order By: Relevance
“…Miziolek et al indicated that excessive intake of vitamin A may deteriorate functioning of vitamin D especially in subjects with a vitamin D deficiency (<50 nmol/l of 25 OH vitamin D), therefore a similar side effect may also appear in patients using ISO. The authors suggested that decreasing the use of ISO after bone injury or continuing the treatment at low dose with a concomitant correction of vitamin D and calcium status 30 . The vitamin D deficiency may be a condition predisposing to osteoporosis and decreased bone mineral density 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Miziolek et al indicated that excessive intake of vitamin A may deteriorate functioning of vitamin D especially in subjects with a vitamin D deficiency (<50 nmol/l of 25 OH vitamin D), therefore a similar side effect may also appear in patients using ISO. The authors suggested that decreasing the use of ISO after bone injury or continuing the treatment at low dose with a concomitant correction of vitamin D and calcium status 30 . The vitamin D deficiency may be a condition predisposing to osteoporosis and decreased bone mineral density 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Experts recommend to stop isotretinoin treatment or at least to reduce the treating dose to 0.5 mg/kg daily (low‐dose isotretinoin), together with correction of Vitamin D and calcium status is suggested to avoid isotretinoin‐induced osteoporosis (Miziołek, Bergler‐Czop, Stańkowska, & Brzezińska‐Wcisło, ). On the other hand, isotretinoin may induce acute rhabdomyolysis that have a negative effect on long bone healing due to muscle weakness particularly muscle flaps in surrounding of the fracture.…”
Section: Safety Of Low‐dose Isotretinoinmentioning
confidence: 99%
“…Os autores relataram casos de ossificação semelhante à observada na Hiperostose Esquelética Idiopática Difusa (do inglês: Diffuse idiopathic skeletal hyperostosis, DISH), fechamento prematuro de epífises e afinamento periosteal, hipercalcemia e osteoporose como reações adversas ao uso da isotretinoina (33). Outro grupo demonstrou o aumento do risco de fraturas deflagrado pela isotetinoina, como consequência do aumento da formação de osteoclastos, responsáveis pela reabsorção óssea e, por conseguinte, pela diminuição da massa óssea cortical (34).…”
Section: Retinoides Na Cicatrização óSseaunclassified